RELASI MAKNA PADA KARYA MUSIK IDGITAF: KAJIAN SEMANTIK TERHADAP LIRIK LAGU-LAGU POP MUSISI INDONESIA - Irma Bela Oktaviana (Jurnal Manajemen Pendidikan, 2025)
This study aims to identify and analyze the types of semantic relations found in Idgitaf’s song lyrics and to understand how these relations convey messages, emotions, and semantic values. The research was conducted online in 2025 using Idgitaf’s song lyrics accessed from the internet as data sources. The population includes all Idgitaf’s songs released between her debut in 2021 and 2025, while the sample consists of 10 purposively selected songs. This study employs a qualitative descriptive approach with content analysis techniques. The data were collected by examining and analyzing the lyrics to identify semantic relations through three stages of analysis: data reduction, data presentation, and conclusion drawing. The results show 31 instances of semantic relations, consisting of 15 antonymy, 9 polysemy, 6 synonymy, and 1 hypernym-hyponym. The dominance of antonymy indicates the use of meaning contrast to strengthen emotional messages, while polysemy, synonymy, and hypernym-hyponym enrich the poetic value of the lyrics. These findings highlight that Idgitaf effectively utilizes semantic relations to express messages and emotions in a simple yet profound manner.